Pengaruh character education training melalui outbound training untuk peningkatan kejujuran dan integritas - Sahril Buchori; Muhammad Ibrahim; Abdul Saman (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
Outbound method is the most effective method to meet the requirements in regarding a training result. The method is effective to build comprehension of a concept and build individual personality such as honesty and integrity. The caracter will continously apply and become a person with a better personality. The research objective is to know the honest and integrity character’s description of the awardee of Bidik Misi in Educational Study Faculty of State University of Makassar (FIP UNM) before and after having the CEt through outbound and to know the effect of CEt through outbound in increasing honest and integrity characters of the awardee of Bidik Misi in Educational Study Faculty of State University of Makassar (FIP UNM). The research is a quantitave research, pre-experimental using One-Group Pretest-Postest Design. The findings is Character Education Training (CEt) through Putbound Training is effective to increase the honest and integrity characters of the awardee of Bidik Misi in Educational Study Faculty of State University of Makassar (FIP UNM).